AISAS Model Analysis of Purchases Millenial Generation in Sovereign Sukuk Based on Cash Waqf Linked Sukuk (CWLS) - Nata Mulyana; Arief Safari; Amrizal Amrizal (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
Cash Waqf Linked Sukuk (CWLS) is a new financial instrument being developed by the Government of Indonesia. The purpose of this study is to test the AISAS Model on the purchase of the millennial generation in Sovereign Sukuk based on CWLS. This study uses a quantitative method using the Structural Equation Model Partial Least Square (SEM PLS) as an analytical tool. The sampling technique used non-probability sampling in obtaining primary data through the distribution of questionnaires or online questionnaires. The respondents of this study came from 207 millennial generation respondents who use Instagram, follow accounts of waqf fund collection institutions, and Whatsapp users. Consisting of 74 men (35.75%) and 133 women (64.25%). The results of the PLS-SEM processing of the AISAS model on retail CWLS purchases show 7 accepted hypotheses, namely variable attention taken to effect positive and significant to interest and search. Then interest has an effect positive and significant on the search, interest variable has an effect positive and significant on the action. Likewise, interest is influential positive, and significant to the Millennial Generation's share of Retail CWLS information, then the search has an effect positive and significant to the action. The action influences positive and significant share activity. while the other 3 hypotheses were rejected because attention no takes effect positive and significant effect on action, attention has no significant effect on the share, and search has no effect significant against shares. This research suggests that institutions related to the development of cash waqf, especially Retail CWLS (BWI, DJPPR, and Islamic banks appointed as LKSPWU) need to reproduce and continuously create interesting content related to money waqf education and social investment through Retail CWLS. The content is delivered through social media such as Instagram, Facebook, and Youtube. In addition, it is necessary to develop online purchasing facilities that are integrated with various online transaction platforms that are currently developing, such as through the marketplace and independent waqf management bodies.